Association between the BCR-ABL gene transcripts and the laboratory hematological profile - Oliveira, Marcelo Braga de (2022)
Objective: This study describes the hematological parameters associated with the BCR-ABL gene transcripts in patients with chronic myeloid leukemia (CML). Methods: We reviewed the results of 100 detectable patients for one of the BCR-ABL gene transcripts. The eligibility criteria were based on the presence of one of the leukemic transcripts (b2a2, b3a2, and b2a2/b3a2) and complete epidemiological and hematological data. The data were obtained from the LabMaster computerized system. The Kruskal-Wallis test was used to compare the medians of the quantitative variables between the transcripts of the BCR-ABL gene and the chi-square test to compare the qualitative ones, adopting the p-value with a level of significance less than or equal to 0.05. Results: Forty-five patients (45%) presented the b2a2 transcript, 24 (24%) the b3a2 transcript and 31 (31%) a b2a2/b3a2 coexpression. Individuals who expressed the b3a2 transcript had higher leukocyte counts and platelet levels, but we found no differences compared with individuals who expressed the other transcript. Conclusion: In this study, the BCR-ABL gene transcripts did not influence the hematological parameters of patients with CML.